PHENOLIC DERIVATIVE COMPOUNDS FROM ERYTHRINA VARIEGATA L. AND BIOACTIVITY AS A TYROSINE KINASE INHIBITOR - Noviany, Iin
The genus Erythrina is a plant that contains secondary metabolites of flavonoids, isoflavonoids, alkaloids, and terpenoids. Natural compounds derived from isoflavonoids mostly isoflavones and pterocarpans, also have been reported anticancer activity shown by various biological properties such as cytotoxic and antioxidant. One of the species is Erythrina variegata L (dadap), which is a plant that is distributed in tropical and subtropical areas. Many studies on this plant have been carried out, but research from Indonesian samples has not been widely carried out, especially on the root barks. In this study, the isolation, characterization, and bioactivity testing of secondary metabolites from the root barks of E. variegata was carried out from Bandung, West Java. Isolation of secondary metabolites from root barks extract of E. variegata L involved several steps, such as extraction, fractionation, and purification using various chromatographic methods. The molecular structure of the isolated compound was determined based on spectroscopic data (MS, 1D-NMR, and 2D-NMR). Three pure compounds have been isolated. One pure compound identified as a flavonoid (flavanone), namely isolonchocarpin (A1), and two pure compounds are isoflavonoid (pterocapen) namely eryvarin E (A2) and eryvarin D (A3). The compounds were then evaluated for their activity as receptor tyrosine kinase inhibitors (EGFR, HER2, HER4, IGFR, InsR, KDR, PDGFR?, and PDGFR?). Only eryvarin E (A2) showed tyrosine kinase inhibitory activity with relatively weak activity against InsR targets.